EVALUASI DISTRIBUSI LOGISTIK PEMILU LUAR NEGERI - Roszamania B. Haji; Rizki Ardelia; Teresa Rachel Ayu Pracheta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Elections are a crucial pillar of democracy where citizens determine leaders through fair and transparent voting processes. Abroad, elections also receive special attention as they involve Indonesian citizens living in various countries. This study aims to evaluate the distribution of election logistics abroad, identify the hindering factors, and provide recommendations for improving the election logistics distribution process in the future. The research method used is descriptive qualitative with a literature study approach. The results show that the main challenges in the distribution of election logistics abroad include the large volume of logistics, delays in logistics delivery, and the scattered distribution of voters across various countries and regions. To overcome these challenges, improved coordination, careful planning, and enhanced competence of logistics management and implementation personnel are required.